2020
DOI: 10.4239/wjd.v11.i7.269
|View full text |Cite
|
Sign up to set email alerts
|

Sodium-glucose cotransporter 2 inhibitors’ mechanisms of action in heart failure

Abstract: Three major cardiovascular outcome trials (CVOTs) with a new class of antidiabetic drugs - sodium-glucose cotransporter 2 (SGLT2) inhibitors (EMPA-REG OUTCOME trial with empagliflozin, CANVAS Program with canagliflozin, DECLARE-TIMI 58 with dapagliflozin) unexpectedly showed that cardiovascular outcomes could be improved possibly due to a reduction in heart failure risk, which seems to be the most sensitive outcome of SGLT2 inhibition. No other CVOT to date has shown any significant benefit on heart failure ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 76 publications
1
14
0
Order By: Relevance
“…For the use of dapagliflozin, Yuan et al found that SUA levels decreased from 347.75 ± 7.75 μmol/L before dapagliflozin treatment to 273.25 ± 43.18 μmol/L after dapagliflozin treatment, with a statistically significant difference ( p = .001), and the SUA‐lowering effect of dapagliflozin could be driven by increasing UA excretion within 1 week of treatment, which may be the mechanism of SGLT‐2 inhibitors in lowering SUA 52 . In addition, dapagliflozin has early cardiorenal benefits, which included anti‐inflammatory, antifibrotic, antioxidative, antiapoptotic properties, renoprotective and haemodynamic effects, as well as attenuation of glucotoxicity, reduction of SUA levels and epicardial adipose tissue, modification of the neurohumoral system and cardiac fuel energetics, and inhibition of the sodium–hydrogen exchange 53 …”
Section: Discussionmentioning
confidence: 99%
“…For the use of dapagliflozin, Yuan et al found that SUA levels decreased from 347.75 ± 7.75 μmol/L before dapagliflozin treatment to 273.25 ± 43.18 μmol/L after dapagliflozin treatment, with a statistically significant difference ( p = .001), and the SUA‐lowering effect of dapagliflozin could be driven by increasing UA excretion within 1 week of treatment, which may be the mechanism of SGLT‐2 inhibitors in lowering SUA 52 . In addition, dapagliflozin has early cardiorenal benefits, which included anti‐inflammatory, antifibrotic, antioxidative, antiapoptotic properties, renoprotective and haemodynamic effects, as well as attenuation of glucotoxicity, reduction of SUA levels and epicardial adipose tissue, modification of the neurohumoral system and cardiac fuel energetics, and inhibition of the sodium–hydrogen exchange 53 …”
Section: Discussionmentioning
confidence: 99%
“…The first class of glucose-lowering drugs that have demonstrated a consistent and robust reduction in the risk of heart failure hospitalization in patients with diabetes make them game-changers in cardiometabolic pharmacotherapy. Additionally, the efficacy in primary and secondary prevention of heart failure has already translated to efficacy in the treatment of heart failure in HFrEF patients with or without diabetes, but they may also be of value in the treatment of HFpEF [ 171 , 172 ]. The potential mechanisms of their action have already been mentioned before.…”
Section: Therapeutic Possibilitiesmentioning
confidence: 99%
“…In this way, SGLT2 inhibitors could synergistically work with angiotensin receptor neprilysin inhibitors (ARNIs). In theory, this would be of value especially in the failing heart when the natriuretic peptides are markedly raised [ 172 , 173 , 174 ].…”
Section: Therapeutic Possibilitiesmentioning
confidence: 99%
“…To date, therapies include treatment with vasodilators, angiotensin-converting enzyme (ACE) inhibitors, and angiotensin receptor blockers (ARBs) as well as beta-blockers and mineralocorticoid receptor antagonists (MRAs) [ 34 , 35 , 36 ]. In addition, the US Food and Drug Administration (FDA) has recently approved the sodium–glucose co-transporter 2 (SGLT2) inhibitors as a novel therapeutic approach to treating HFrEF patients, irrespective of the presence or absence of type 2 diabetes (T2D) [ 37 , 38 , 39 , 40 ]. However, the risk to patients remains high, and further studies are required to define new pharmacological approaches [ 34 , 35 , 36 ].…”
Section: Introductionmentioning
confidence: 99%